A Lifetime of Fishing - Dennis, David (Choice Publishing, 2021)
David Dennis is a dedicated angling enthusiast and has represented Ireland at the World Lure Championships on eight occasions. _x000D_In his new book, 'A Lifetime of Fishing,' David relates a collection of light hearted, short fishing stories including a wealth of knowledge gained from a lifetime spent fishing, sometimes venturing into the darker side of the angler's psyche, and includes some of fishing's best kept secrets.